Emotional Intelligence Profiles in College Students and Their Fathers’ and Mothers’ Parenting Practices - García Linares, Maria Cruz (J Adult Dev, 2018)
The present study has two objectives: first, to analyze whether the dimensions that make up emotional intelligence (attention, clarity, and repair) give rise to different profiles of university students, and secondly, to determine whether these different profiles are differentially associated with the parenting practices that students report with regard to their fathers and mothers. Results obtained indicate the existence of different profiles of college students. The profile that corresponds to adequate emotional skills presents a lower score in attention, but higher scores in clarity, and especially in mood repair. The other two profiles are inadequate, in the first case because a higher score in emotional attention is accompanied by low scores in mood repair, and in the second case because low scores are presented in all three dimensions. Likewise, we verified the existence of significant differences in the educational practices of parents, the adequate profile is characterized by greater use of parenting dimensions considered to be positive, and at the same time, lower scores on dimensions considered to be negative. One of the dysfunctional profiles is associated with higher scores in positive practices, and is also associated with higher scores in practices considered to produce a negative effect. The second dysfunctional profile is associated with higher scores on the dimensions considered to be negative and lower scores on positive dimensions.